3PC-020 Dose-banding of nivolumab. (2nd March 2018) - Frapsauce, A; Laugueux, A; Lester, MA
Abstract : Background: Nivolumab is a human monoclonal antibody used in the pneumology unit to treat patients with metastatic non-small cell lung cancer (NSCLC) with progression on, or after, platinum-based chemotherapy. Nivolumab is administered intravenously at a dose of 3 mg/kg every 2 weeks or at a dose of 240 mg (dose based on the median body weight of 80 kg in patients in American clinical trials). Purpose: In order to meet the increasing demand for chemotherapy in our hospital we consider introducing a system of standardised dose-banding. Material and methods: In making an assessment of nivolumab prescriptions and of the patient characteristics who received nivolumab in 2016, we analysed the medical records on our chemotherapy software Asclepios ® . Results: In 2016, our centralised reconstitution unit had prepared 472 nivolumab doses. Bodyweights of ours patients were clustered: 43 to 114 kg, with a median of 72 kg. The use of banded doses to give doses within 10% of the prescribed dose was considered acceptable practice by our prescribers. Therefore a standard dose of 240 mg could be administered to patients between 74 and 88 kg and a standard dose of 198 mg could be administered to patients between 60 and 73 kg. In view of our patients' bodyweights in 2016, 40% of the prepared nivolumab could have been matched with the 240 mg standard dose and 36% with the 200 mg (rounded value of 198 mg) standard dose. Following this analysis, a meeting between the pneumology unit and the pharmacy allowed the creation of two nivolumab protocols: 200 mg (for weights≤73 kg) and 240 mg (for weights>73 kg). Conclusion: Dose-banding of nivolumab is effective since May 2017. Previous protocols were replaced by the two new protocols. This standardisation permits a reduction in waiting times for patients (nivolumab doses were prepared the day before) and reduces the waste when treatments are deferred (due to ability to re-asign the preparations). References and/or Acknowledgements: Vidal, Asclepios, medical records. No conflict of interest